Desarrollo de la dentición y su biología molecular - Barhoum Farai, Habib Salim; Celis Sánchez, Marietta (Revista Estomatología, 1996)
The dental development is a process which involves man celular and molecular changes and interactions. It is covered under a strict genetic control and works as a closed circuit between the gene expression and the factors of growth. When endocrine regulation is added, these events of craneofacial growth are complex and unpredictible.